Mega solid bone cyst in iliac region from primary hyperparathyroidism: a case report - Francesco Rosario Campo; Federico Di Sacco; Antonio D’Arienzo; Edoardo Ipponi; Fabio Cosseddu; Vanna Bottai; Sebastiano Barreca; Lorenzo Andreani; Paolo Domenico Parchi (Journal of Medical Case Reports)
Abstract Background Aneurysmal bone cysts are benign, locally aggressive bone lesions that commonly affect young adults and adolescents. These cysts, which may cause pain, fractures, or deformities, are often associated with vascular or abnormal bone resorption processes. Though their etiology is not fully understood, an intriguing and rarely discussed correlation between aneurysmal bone cysts and endocrine disorders, particularly primary hyperparathyroidism, has been reported. Hyperparathyroidism, usually resulting from a parathyroid adenoma, promotes osteoclastic activity, which can lead to bone resorption and potentially the formation of aneurysmal cysts. The diagnosis of hyperparathyroidism can be challenging, especially in the absence of characteristic clinical signs. Case presentation A 47-year-old Albanian Caucasian female individual, with a body mass index of 40, presented with coxalgia and an incidental finding of an osteolytic lesion in the right sacral wing on pelvic X-ray. Subsequent imaging, including magnetic resonance imaging and computed tomography, confirmed the presence of a large aneurysmal bone cyst. Despite its size, traditional surgical interventions were not pursued owing to the discovery of primary hyperparathyroidism, as indicated by elevated serum calcium and parathyroid hormone levels. A parathyroid ultrasound revealed an atypical adenoma in the left lower parathyroid, confirming the diagnosis of hyperparathyroidism. The patient underwent successful parathyroidectomy and left thyroid loboistectomy with a favorable outcome. Postsurgical follow-up revealed normalization of metabolic parameters and clinical resolution of symptoms, with stable dimensions of the sacral cyst. Conclusion This case emphasizes the importance of thorough diagnostic evaluation in patients with bone lesions, particularly in those with risk factors for metabolic bone disorders. Primary hyperparathyroidism, although rare, can manifest with bone abnormalities such as aneurysmal cysts. A multidisciplinary approach, including timely diagnosis and surgical intervention, is crucial for optimal management and preventing long-term complications. Regular follow-up and monitoring of metabolic parameters are key to ensuring successful outcomes.